Minerals contributing to human health and well-being - Ekaterina V. Kulchavenia (LLC "MEDIAFORMAT", 2021)
The gut microbiome is vital for normal human body functioning. The etiological and pathogenetic significance of increased intestinal permeability in disorders of various organs and systems seems to be certain. The term "microbiota-gut-brain axis" has been defined; the crucial role of the microbiota-gut-brain axis in neurological disorders has been confirmed. Gut microbiome not only contributes to digestion, metabolism and immunity, but also mediates sleep and mental health of the host via microbiota-gut-brain axis. Such elements as zinc and selenium are essential to maintain the microbial balance in the gut. Zinc contributes to gut homeostasis and Paneth cell function. Zinc has a direct impact on gut microbiota composition (for example, on some species of Staphylococcus), modulates gut microbiota reducing the fatal entry of bacteria into the bloodstream and lymphatic vessels. Thus, zinc alters microbiome due to direct cytotoxic / cytostatic effect on certain bacteria, such as staphylococci. Zinc possesses therapeutic effect in gastrointestinal infections and diarrhea. Bacterial translocation may be also reduced with Rebamipide possessing cytoprotective and antioxidant activity. Selenium in the form of selenoproteins has a number of functions in normal health and metabolism. Selenium contributes to immune system functioning and to progression of HIV to AIDS. Selenium deficiency results in cardiovascular diseases, infertility, myodegenerative disorders, and cognitive decline.